2021
DOI: 10.3892/or.2021.8092
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of hydrogen on cervical cancer suppression revealed by high‑throughput RNA sequencing

Abstract: Cervical cancer is considered one of the diseases with the highest mortality among women and with limited treatment options. Hydrogen (H 2 ) inhalation has been reported to have a variety of tumor-suppressive effects, but the exact mechanism remains unclear. In the present study, HeLa cervical cancer cells and HaCaT keratinocytes treated with H 2 , and a HeLa xenograft mouse model subjected to H 2 inhalation were established. TUNEL, Cell Coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…In addition, Shang et al, (2018) displayed the therapeutic potential of hydrogen in ovarian cancer. The in vivo studies showed a similar result to Chu et al, (2021)'s study in which tumour growth was suppressed after 6 weeks of hydrogen inhalation. This can be explained through their in vitro studies in which hydrogen can inhibit cancer cell proliferation, invasion, and colony formation.…”
Section: Effects Of H2 Based On Types Of Cancersupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, Shang et al, (2018) displayed the therapeutic potential of hydrogen in ovarian cancer. The in vivo studies showed a similar result to Chu et al, (2021)'s study in which tumour growth was suppressed after 6 weeks of hydrogen inhalation. This can be explained through their in vitro studies in which hydrogen can inhibit cancer cell proliferation, invasion, and colony formation.…”
Section: Effects Of H2 Based On Types Of Cancersupporting
confidence: 81%
“…A study on cervical cancer demonstrates how H2 had a much lower ROS level compared to the control group (p < 0.01). This suggests the treatment's role in reducing the oxidative stress level even in animal studies (Chu et al, 2021). A common effect also seen in animal models is the suppression of tumour growth through various antitumor mechanisms.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…To assess whether oxyhydrogen would affect the cell viability and proliferation of immortalised immune cells (TK6-B-lymphocytes), this novel enquiry focused on the effects of infusing oxyhydrogen gas into cell culture media in an attempt to simulate the most likely dispersal and retention patterns of the aforementioned gas in the blood or serous fluids. Although it is recognised that an increase in pH may have influenced some aspects of cellular activity, the results of further analysis are congruent with early [56,57] and contemporary research [44][45][46]. Interestingly, Figure 6 evinces a distinct increase in cells in the Sub G1 phase at 24 (Control: 9% vs. 46%) and 48 h (Control: 18% vs. 40%) after oxyhydrogen treatment, concomitant with marked decreases in growth phases 1 (24 h: Control: 39% vs. 25%; 48 h: Control: 37% vs. 31%) and 2 (24 h: Control: 28% vs. 10%; 48 h: Control: 19% vs. 10%).…”
Section: Discussionsupporting
confidence: 59%
“…To date, the pro-apoptotic, anti-tumor effects of hydrogen therapies on solid tissue cancers have been relatively well-studied [7,8,23,29,[40][41][42][43][44][45][46]. However, investigations into leukaemic and lymphoma cell lines remain largely unexplored.…”
Section: Rationalementioning
confidence: 99%